Case Study of Earthquake Resistant Structure and Its Recent Innovation In Construction (International Journal of Innovative Research in Engineering & Management, 2022)
Earthquakes may create various kinds of  causalities like loss of life and damage of property  depending upon its magnitude; causalities could range  from small property damage to landslides and a long  range of liquefaction. Secondary effects like fire;  blockage on services such as water supply, electricity,  and transportation; and communication disruption are  even more disastrous.Man-made infrastructures are  however the major contributor of casualties during  earthquake devastations. These structures therefore  should be carefully designed and constructed.It is very  important to develop new technologies to minimize these  losses. Thus, we started to do research regarding these  new techniques and to improve our knowledge and  become aware of these recent methods and their usage in  our daily life to optimize earthquake effects on our  structures. We cannot make fully earthquake-proof  structures but we will reduce its damage and make  structures earthquake resistant. In this research paper, we  will discuss modern technologies that make our structure  earthquake resistant.
Keywords: Advanced Techniques; Earthquake; Effective Designs Process; Ideal Resistant Ratio